ENHANCED HAPTIC INTERFACE FOR ROVER TELEOPERATION - Rute Luz; Pereira; Ferreira; Krueger; Corujeira, J.; José Luís Silva / José L. Silva / J. L. Silva; Rodrigo Ventura (16th Symposium on Advanced Space Technologies in Robotics and Automation, 2022)
A well know challenge in rover teleoperation is the lack of situational awareness of the operator. This often leads to an erroneous perception of the status of the rover and its surrounding environment and, consequently, lead to faulty decision making. We conceptualise a novel teleoperation method to drive a rover in the context of planetary exploration. The proposed teleoperation interface employs a force feedback device to control the navigation of a rover while providing haptic feedback to ensure the operator’s appropriate situational awareness. In particular, we will design and iterate proprioceptive cues (e.g. to convey the rover’s attitude) and vibratory cues (e.g. to convey traction losses of the rover’s wheels) to enhance the situational awareness of the astronaut. Finally, the implemented rover control and feedback will be systematically evaluated and iterated through user studies using a real robot in an analog environment.